Governance Structures for Local Economic Development in Croatia - Ivana Rasic-Bakaric; Marijana Sumpor; Jelena Sisinacki (European Regional Science Association (ERSA), 2005)
Who should take care of local economic development in Croatia? This question seems trivial, however, there are still some open questions. According to current legislation, local economic development is an administrative task of the 21 counties, the current units of regional self-government. On the other hand, the cities and municipalities as units of local self-government regularly get involved in economic development activities, though this is not directly defined in the legislation. There is a contradiction concerning development capacity of cities and counties. Cities attract population and economic activity and are usually stronger than counties in terms of financial and human resources that are necessary for economic development activities. This research will question if the existing administrative-territorial setup and functions of counties in Croatia correspond to the needs of economic growth and development on local level. It is also intended to get some insights from contemporary concepts that derive from trade theory, location theory and economic geography. Governance relations between bigger cities and counties in fostering local economic development in Croatia will be examined. For this purpose, local and regional data will be analyzed and through the discussion on existing governance structures, qualitative insights on the appropriateness of the current situation will be presented. The main goal of this research paper is to find quantitative and qualitative justification for an appropriate governance structure for fostering local economic development in Croatia.
Keywords: 330